Determination of Resistant Starch Assimilating Bacteria in Fecal Samples of Mice by In vitro RNA-Based Stable Isotope Probing - Herrmann, Elena; Young, Wayne; Rosendale, Douglas; Conrad, Ralf; Riedel, Christian U.; Egert, Markus (Frontiers in Microbiology, 2017)
The impact of the intestinal microbiota on human health is becoming increasingly appreciated in recent years. In consequence, and fueled by major technological advances, the composition of the intestinal microbiota in health and disease has been intensively studied by high throughput sequencing approaches. Observations linking dysbiosis of the intestinal microbiota with a number of serious medical conditions including chronic inflammatory disorders and allergic diseases suggest that restoration of the composition and activity of the intestinal microbiota may be a treatment option at least for some of these diseases. One possibility to shape the intestinal microbiota is the administration of prebiotic carbohydrates such as resistant starch (RS). In the present study, we aim at establishing RNA-based stable isotope probing (RNA-SIP) to identify bacterial populations that are involved in the assimilation of RS using anaerobic in vitro fermentation of murine fecal material with stable [U13C] isotope-labeled potato starch. Total RNA from these incubations was extracted, processed by gradient ultracentrifugation and fractionated by density. 16S rRNA gene sequences were amplified from reverse transcribed RNA of high and low density fractions suspected to contain labeled and unlabeled RNA, respectively. Phylogenetic analysis of the obtained sequences revealed a distinct subset of the intestinal microbiota involved in starch metabolism. The results suggest Bacteroidetes, in particular genera affiliated with Prevotellaceae, as well as members of the Ruminococcacea family to be primary assimilators of resistant starch due to a significantly higher relative abundance in higher density fractions in RNA samples isolated after 2 h of incubation. Using high performance liquid chromatography coupled to isotope ratio mass spectrometry (HPLC-IRMS) analysis, some stable isotope label was recovered from acetate, propionate and butyrate. Here, we demonstrate the suitability of RNA-SIP to link specific groups of microorganisms with fermentation of a specific substrate. The application of RNA-SIP in future in vivo studies will help to better understand the mechanisms behind functionality of a prebiotic carbohydrate and its impact on an intestinal ecosystem with potential implications for human health.